1984
DOI: 10.1007/bf00040341
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced adventive embryogenesis resulting from plasmolysis of cultured wild carrot cells

Abstract: Adventive embryogenesis in vitro-grown somatic ceils ofDaucus carota L. was increased three-fold by a 45 rain plasmolysis pre-treatment using 1M sucrose solutions. A high degree of synchronous development also resulted from this treatment. The enhancement of embryogenesis is interpreted as an increase in the regeneration of cells which have become physiologically somewhat isolated from the tissue of their origin by the plasmolysis-caused rupture of plasmodesmata. Possible causes of the increased synchrony are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 13 publications
1
22
0
2
Order By: Relevance
“…Accordingly, physical treatments that result in cell isolation may stimulate embryogenesis. Severance of plasmodesmata through desiccation-induced plasmolysis enhanced embryogenesis in carrot [30] and rice [31]. In Dysosma [32], East Indies walnut, and kardofan, tissue maceration in the absence of exogenous growth regulators was sufficient to induce somatic embryos [33,34].…”
Section: B Effects On Intercellular Interactionsmentioning
confidence: 99%
“…Accordingly, physical treatments that result in cell isolation may stimulate embryogenesis. Severance of plasmodesmata through desiccation-induced plasmolysis enhanced embryogenesis in carrot [30] and rice [31]. In Dysosma [32], East Indies walnut, and kardofan, tissue maceration in the absence of exogenous growth regulators was sufficient to induce somatic embryos [33,34].…”
Section: B Effects On Intercellular Interactionsmentioning
confidence: 99%
“…It has been demonstrated that other stimuli also induce somatic embryogenesis. For example, in D. carota somatic embryogenesis can be induced by some kind of stress, including osmotic shock with sucrose or sodium chloride (Wetherell 1984;Kamada et al 1989) or the presence of heavy metals-cobalt, nickel, zinc and cadmium (Kamada et al 1989;Kiyosue et al 1990)-without any application of auxin. Additionally, somatic embryogenesis induction by stress-related stimuli is not only restricted to carrot.…”
Section: Exogenous Compounds Involved In the Induction Of Somatic Embmentioning
confidence: 99%
“…The better regeneration from small cell aggregates could also be due to destruction of adjacent cells, creating a single cell or a very small aggregate. Wetherell (1984) reported that creation of single cells by disruption of plasmodesmata promoted regeneration, possibly because the single cells were prevented from contact with neighbour cells. Neither zygotic embryos nor single somatic embryogenic cells possess, plasmodesmata, and it may be due to this that they develop analogously (Wethereli 1984).…”
Section: Transplantationmentioning
confidence: 99%